The Use Of ICT By Teachers In Implementing A Competency-Based Curriculum At Elementary School - Putri Windi Lailatur Rahmi; Devy Aisyah; Amrina Amrina (Lingeduca: Journal of Language and Education Studies, 2023)
Implementation of the curriculum in elementary school based on the use of ICT by educators. Nowadays, ICT has developed from time to time, this requires all educators to be able to use ICT. As educators, of course, they must be able to master technology, especially for the learning process for students. This ICT learning does not only exist in public schools, but also in elementary school By learning to use ICT, and educators who use it can also master it, learning will be easier for both educators themselves and students. The purpose of this research itself refers to how the use of ICT by educators in elementary school in order to implement the competency curriculum in elementary school. The research was conducted using in-depth interviews with educators at elementary school through the WhatsApp application with a qualitative method. The results of the research are that the use of ICT for educators is quite developed, even ICT is very helpful for educators in providing material that is easily understood by students. The use of ICT in elementary school is very beneficial for educators and for students, with ICT in learning it makes it very easy for students to understand the material provided, moreover students are very happy with things that attract their attention so that the material provided will be easier to understand. The limitations of this research are that the researcher did not make a report on what percentage of educators can use ICT, as well as the extent to which educators and researchers have only studied one elementary school. Therefore, it is hoped that future researchers can conduct better and more complete research